Proceedings of the Fifteenth Workshop on Innovative Use of NLP for Building Educational Applications 2020
DOI: 10.18653/v1/2020.bea-1.8
|View full text |Cite
|
Sign up to set email alerts
|

Can Neural Networks Automatically Score Essay Traits?

Abstract: Essay traits are attributes of an essay that can help explain how well written (or badly written) the essay is. Examples of traits include Content, Organization, Language, Sentence Fluency, Word Choice, etc. A lot of research in the last decade has dealt with automatic holistic essay scoring -where a machine rates an essay and gives a score for the essay. However, writers need feedback, especially if they want to improve their writing -which is why traitscoring is important. In this paper, we show how a deep-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…For the purposes of this review, those associated solely with the quality of the products, writing reports or openended constructed responses, such as spelling, or grammar automatic reviewers are not included. On the other hand, research on the quality of writing, such as sentence fluency, clarity, and coherence, has been researched in the past based on the classification of engineering features [45], [59]. Recent developments using deep learning methods, such as the one proposed by Mathias & Bhattacharyya [45] based on a hierarchical Convolutional Neural Network and Long Short-Term Memory (CNN-LSTM) architecture or in attention-based Recurrent Convolutional Neural Network presented by Dong et al [9], show promising results generalizing different aspects of writing quality for holistic grading and richer feedback.…”
Section: Student Problem-solving Performancementioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of this review, those associated solely with the quality of the products, writing reports or openended constructed responses, such as spelling, or grammar automatic reviewers are not included. On the other hand, research on the quality of writing, such as sentence fluency, clarity, and coherence, has been researched in the past based on the classification of engineering features [45], [59]. Recent developments using deep learning methods, such as the one proposed by Mathias & Bhattacharyya [45] based on a hierarchical Convolutional Neural Network and Long Short-Term Memory (CNN-LSTM) architecture or in attention-based Recurrent Convolutional Neural Network presented by Dong et al [9], show promising results generalizing different aspects of writing quality for holistic grading and richer feedback.…”
Section: Student Problem-solving Performancementioning
confidence: 99%
“…Originated from the scoring point of view, automated essay scoring (AES) has a vast tradition in machine learning and natural language processing [38]. Relevant to the assessment of CPS, recent developments in AES research [15] [27], [24], [29], [45], [65], [67], [68] have been motivated by increasing attention to developing argumentation skills in STEM education to deepen scientific and critical thinking. Deep learning architectures based on LSTM with or without attention, hierarchical CNN, and the use of pre-train language models like BERT have successfully been able to extract high-order features associated with argumentation features.…”
Section: Argumentative Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, most of the approaches focused on modeling language proficiency as a single variable. Although there is some research focusing on multiple dimensions of language proficiency (Lee et al, 2009;Attali and Sinharay, 2015;Agejev and Šnajder, 2017;Mathias and Bhattacharyya, 2020), none of them focused on non-English languages or used recent multilingual pre-trained models such as BERT. In this paper, we focus on this problem of multi-dimensional modeling of language proficiency for three languages-German, Italian, and Czech-and explore whether recent research on multilingual embeddings can be useful for non-English AES.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments showed that the accuracy of the different ML models ranged between 80%-96% for the different reflective essay metrics. Mathias and Bhattacharyya (2020) explored the use of deep learning models to automate the essay grading process. To that end, the authors used the ASAP AEG dataset that described differed essay sets with multiple essay traits such as Content, Organization, Word Choice, Sentence Fluency, and Conventions (Mathias and Bhattacharyya, 2018).…”
Section: Challenge Descriptionmentioning
confidence: 99%